APLIKASI PELAYANAN KESEHATAN PADA PUSKESMAS - Helda Yunita; Dina Dina (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2021)
In general, at the puskesmas there are many activities such as treatment of diseases, health checks, laboratory tests, immunization of toddlers, and others. The large number of patients causes much problems in archiving data on patient visits for treatment, as well as patient medical records. Meanwhile, the drug data collection is made manually, by conducting a stock of names every month, to check how many drugs have been used by the Puskesmas. After that, at the end of each month, the person in charge of the pharmacy does a recapitulation but there is a discrepancy between the checking results and the remaining stock. To overcome this manual process, a desktop-based application was created to build a system to simplify all the necessary processes, such as the patient visit archiving process which functions to report patient visit data, process medical records directly on the system to make it easier to store data, the process of calculating drug stock. available and do not need stock of name manually. This health service application is made using Microsoft Visual Basic 2010 which stores patient data, medical records, medical personnel, and available drugs so that it can make it easier for medical personnel to record, search, report patient visit data, medical records and facilitate stock calculations drugs in accordance with applicable health service operational standards.